2004
DOI: 10.1007/s00268-004-7302-y
|View full text |Cite
|
Sign up to set email alerts
|

Combined Assessment of β‐d‐Glucan and Degree of Candida Colonization before Starting Empiric Therapy for Candidiasis in Surgical Patients

Abstract: The purpose of the study was to investigate whether examination for plasma beta-D-glucan, a cell wall constituent of fungi, is useful for selecting surgical patients with Candida colonization who would benefit from empiric antifungal therapy. We administered fluconazole to postoperative patients with Candida colonization who have risk factors for candidemia and complained of persistent fever despite prolonged antibacterial therapy. We then analyzed the clinical outcomes regarding the number of sites colonized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 43 publications
1
25
1
1
Order By: Relevance
“…Although previous studies have shown the usefulness of BDG for the diagnosis of IC in surgical patients [6,22,25], our findings confirm that BDG is highly specific for a cutoff value of 259 pg/mL but with a very low sensitivity (51.6 %). CAGTA (negative/limit-positive) has a better sensitivity than BDG but its specificity is lower.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Although previous studies have shown the usefulness of BDG for the diagnosis of IC in surgical patients [6,22,25], our findings confirm that BDG is highly specific for a cutoff value of 259 pg/mL but with a very low sensitivity (51.6 %). CAGTA (negative/limit-positive) has a better sensitivity than BDG but its specificity is lower.…”
Section: Discussionsupporting
confidence: 70%
“…This finding is clinically relevant not only for the population to which the prediction rule can be applied, but also because it is very easy to remember and may help intensivists to decide when to start antifungal treatment. A few studies have investigated the predictive value of BDG on IC in non-neutropenic critically ill patients [21][22][23][24][25]. Elevated concentrations of BDG have been reported to be associated with other fungi, such as Pneumocystis jirovecii infections [26], Gram-positive and Gram-negative bloodstream infections, exposure to gauze or other materials that contain glucans, biofilms on vascular catheters, hemodialysis, and administration of a,b Superscripts indicate significant differences (P \ 0.05) among rates of BDG and positive CAGTA values among the three study groups Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 12 false M-positive sera, only 3 were BG positive, which indicates less cross-reaction. However, false-positive BG results have been described after hemodialysis on cellulose membrane (18), after contamination by environmental BG (7), after surgery (contamination by gazes), after treatment with immunoglobulin or antitumoral polysaccharides such as lentinan and schizophyllan (29), or during some bacterial infections (23). We observed four positive BG results among six hemodialysis patients and seven other "false BG-positive" results in the group at risk for candidemia.…”
Section: Discussionmentioning
confidence: 71%
“…The ability of C. albicans to attach to and colonize mucosal tissues is a risk factor for disseminated candidiasis (25,42), and three of the candidal proteins tested here have already been associated with mediating interactions with host epithelia. Als3p has been shown to function as an invasin, inducing endocytosis and uptake of C. albicans into endothelial and epithelial cells by targeting N-cadherin and E-cadherin, respectively (35).…”
Section: Discussionmentioning
confidence: 99%